Video supported critical thinking test in the kinetic theory of gases: validity and reliability. Issue 3 (February 2019) - Silvianty, A; Suhandi, A; Setiawan, W
Abstract: This study is conducted to figure validity and reliability of Video Supported Critical Thinking Test (VSCT-Test). VSCT-Test has already been constructed to evaluate students' critical thinking skills in Physics subjects. The study used the descriptive quantitative method. Seventy students of a high school in West Bandung Regency have been chosen with purposive technique sampling. The VSCT Test was constructed, according to five critical thinking categories framework developed by Tiruneh consisting of 1) Reasoning, 2) Hypothesis Testing, 3) Argument Analysis, 4) Likelihood and Uncertainty Analysis, and 5) Problem Solving and Decision Making. VSCT-Test validity was determined through expert judgment involving construct validity and content validity, whereas VSCT-Test reliability was concluded through field testing with the test-retest method. The results showed that all VSCT-Test items that were constructed had met a good construct validity as well as content validity and had high reliability characterized by reliability index of 0.82. Thus, this indicates that the VSCT-Test instrument has good quality and suitable for measuring the critical thinking skills of high school students.